Liberal Feminism in Novel Broken Strings and Its Relevance to Indonesian Language Learning in Madrasah Aliyah - Siti Jamila; Wahyu Lestari; Ahmad Ilzamul Hikam (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study aims to describe the representation of liberal feminism in Aurelie Moeremans's novel Broken Strings and to examine its relevance to Indonesian language learning among eleventh-grade students at MA ZAHA 3. A descriptive qualitative approach was employed. The primary data source was the novel itself, while secondary data were obtained through interviews with four eleventh-grade students and relevant scholarly literature on liberal feminism. Data were collected through literature review, documentation of textual excerpts, and semi-structured interviews, and were analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing, with source triangulation used to establish trustworthiness. The findings reveal five recurring forms of injustice experienced by the female protagonist—psychological violence, physical violence, domination, forced dependency, and unequal treatment—alongside five corresponding forms of resistance and empowerment: courage in confronting adversity, resistance to oppression, efforts toward recovery, growing independence, and autonomous decision-making. These patterns collectively constitute a representation of liberal feminism centered on individual freedom, equality of rights, and women's pursuit of autonomy. Student interviews further indicate that the novel is considered linguistically accessible and thematically relevant, containing social and moral values pertinent to adolescent readers, supporting its potential use as literary teaching material in Indonesian language instruction at the senior secondary level.